Metabolic engineering considerations for the heterologous expression of xylose-catabolic pathways inSaccharomyces cerevisiae - Jeong, Deokyeol; Oh, Eun Joong; Ko, Ja Kyong; Nam, Ju-Ock; Park, Hee-Soo; Jin, Yong-Su; Lee, Eun Jung; Kim, Soo Rin (PUBLIC LIBRARY SCIENCE, 2020)
Xylose, the second most abundant sugar in lignocellulosic biomass hydrolysates, can be fermented bySaccharomyces cerevisiaeexpressing one of two heterologous xylose pathways: a xylose oxidoreductase pathway and a xylose isomerase pathway. Depending on the type of the pathway, its optimization strategies and the fermentation efficiencies vary significantly. In the present study, we constructed two isogenic strains expressing either the oxidoreductase pathway (XYL123) or the isomerase pathway (XI-XYL3), and delved into simple and reproducible ways to improve the resulting strains. First, the strains were subjected to the deletion ofPHO13, overexpression ofTAL1, and adaptive evolution, but those individual approaches were only effective in the XYL123 strain but not in the XI-XYL3 strain. Among other optimization strategies of the XI-XYL3 strain, we found that increasing the copy number of the xylose isomerase gene (xylA) is the most promising but yet preliminary strategy for the improvement. These results suggest that the oxidoreductase pathway might provide a simpler metabolic engineering strategy than the isomerase pathway for the development of efficient xylose-fermenting strains under the conditions tested in the present study.
Keywords: RECOMBINANT SACCHAROMYCES-CEREVISIAE; PENTOSE-PHOSPHATE PATHWAY; IMPROVES ETHANOL-PRODUCTION; XYLITOL DEHYDROGENASE; FUNCTIONAL EXPRESSION; ADAPTIVE EVOLUTION; ANAEROBIC GROWTH; UP-REGULATION; ACETIC-ACID; ISOMERASE